Factors Determining Social Media Marketing Adoption of Micro, Small and Medium Enterprises (MSMEs) in the Northern Province, Sri Lanka - Shanmuganathan, K.; Shivany, S. (Wayamba Journal of Management, 2021)
MSMEs are the backbone of any nation. After the end of the civil war in 2009, people from the Northern Province of Sri Lanka started MSMEs, and that should be run on the virtual market and the physical market for business survival. This study explores the factors determining social media marketing adoption by MSMEs in the Northern Province of Sri Lanka. In this study, data were collected from 10 owners or managers of MSMEs in the research area using multiple case study-based qualitative methods of indepth interviews. The research samples were selected using the purposive sampling technique. There were 12 factors explored such as perceived ease of use, internal and external influencers, technological factors, external institutional pressures, business sustenance, usage of smartphones, observability of market happenings, links among social media platforms, unique features, two-sided benefits, two-way cost reduction and new normal context as findings of the study.
Keywords: Micro Small and Medium Enterprises (MSMEs); Social Media; Social Media Marketing Adoption; The Northern Province of Sri Lanka